Transition of the dominant charge accumulation mechanism at a Gas‐solid interface under DC voltage. Issue 15 (15th June 2020) - Luo, Yi; Tang, Ju; Pan, Cheng; Pan, Zijun; Meng, Guodong
Abstract : In this study, a simulation model of surface charge accumulation on a basin‐type insulator was constructed. Three accumulation mechanisms were considered, i.e. electrical conduction within the gas, electrical conduction through the insulator and along insulator surface. For the gas electrical conduction, the generation, diffusion, drift and recombination of charge carriers in SF6 were taken into consideration. The surface conductivity is treated by directly defining parameters instead of surface thin layer, which improves the calculation range of surface conductivity in ion flow model. Additionally, surface charge accumulation characteristics with different parameters were studied. The results indicated that the polarity of surface charge would change with the ion pair generation rate, volume conductivity and surface conductivity. Based on the surface charge and electric field distributions, it was found that the dominant surface charge accumulation mechanism changes from volume conduction to gas conduction as the ion pair generation rate increases. When the volume conductivity increases from 1 × 10 −19 to 1 × 10 −14 S/m, the dominant mechanism changes from gas conduction to volume conduction. Furthermore, as the surface conductivity increases, the dominant mechanism is surface conduction. The proposed study is helpful for understanding the mechanism of surface charge accumulation and provides insight into charge accumulation inhibition.